A time-varying Gramian based model reduction approach for Linear Switched Systems. Issue 2 (2020) - Hossain, Md. Sumon; Trenn, Stephan
Abstract: We propose a model reduction approach for switched linear system based on a balanced truncation reduction method for linear time-varying systems. The key idea is to approximate the piecewise-constant coefficient matrices with continuous time-varying coefficients and then apply available balance truncation methods for (continuous) time-varying systems. The proposed method is illustrated with a low dimensional academic example.